The aesthetics of (digital) machine sculpture automatization, mechanization, and mathematization in Minimal, Serial, Conceptual, and Computer Art - Rottmann, Michael ca. 20. Jh (2023)
Today’s 3D-printed digital sculpture can be traced back—not only in a technical sense—to the 1960s, when our digital culture developed. Using the examples of pioneers Robert Mallary and Charles Csuri, this paper reconstructs and distinguishes computer-based productions of sculpture, its reception, and its ontology. One focus is the discourse of sculpture, image, and form. A comparison with Minimal, Serial, and Conceptual Art is suggested not only because Minimal Art was a hot spot of sculptural discourse, but also because it reveals correspondences between digital and non-digital arts, which exist on the level of draft, production, and discourse: a creation with certain machines, mathematization, automatization, mechanization, and a 2D/3D-discourse.It will be argued that the examined digital and non-digital artforms in the 1960s, the time of pre-post-digital art, are only understandable in relation to each other and their common historical con-text: cybernetics, systems theory, the Cold War, and computerization. Taking the cultural-historical and politico-economic context into account, it will be demonstrated that one can identify specific reactions to digital technology and media and its impacts on art and society—which is why I call the non-digital artforms "co-digital art."
Keywords: Mallary, Robert -- 1917-1997; Csuri, Charles A. -- 1922-; Geschichte 1960-2021; Plastik; Computerkunst; 3D-Technologie; Virtualisierung; Ästhetik; Digitalisierung